As teorias de desemprego e as políticas públicas de emprego - Zylberstajn, Hélio (1999)
This is a theoretical article about unemployment. First, the authors offer some concepts and definitions related to the situation of unemployment. Second, they survey the main microeconomic unemployment theories, which includes models such as job search, intertemporal substitution, signaling, efficiency wages, sectoral shifts, and hysteresis. Finally, they briefly comment on the implications of the reviewed theories for public policies aimed to combat unemployment, and they conclude that active policies seem to be better than passive policies.